Characterisation of antibody responses induced by BCG and other TB vaccines to inform future vaccine design - Peralta Alvarez, MP (2023)
Tuberculosis (TB) remains a pressing global health challenge. The focus of TB vaccine research traditionally centres on either enhancing BCG's efficacy or identifying a suit-able alternative. Within this context, antibody responses, a potentially relevant corre-late of protection, are inadequately explored. This thesis seeks to underscore the im-portance of understanding antibody-mediated immunity against Mycobacterium tuber-culosis (M.tb) and its implication for vaccine development. Firstly, the optimisation of Systems Serology assays provided a refined methodology for profiling post-vaccination antibody responses in both humans and Non-human primates (NHP). Secondly, my findings illuminate the influence of BCG immunisation routes on induced antibody re-sponses. Notably, intradermal (ID) BCG showed superior PPD-specific IgG and IgA responses when compared to aerosol (AE) BCG in serum, while AE BCG induced PPD-specific IgA in human bronchoalveolar lavage fluid (BALF). Intravenous (IV) BCG in NHPs was associated with superior protection and enhanced antibody titre, avidity, and opsonisation. Thirdly, the introduction of a live attenuated M.tb vaccine candidate, MTBVAC, demonstrated robust antibody-mediated responses, potentially offering an advantage over BCG. An inverse correlation between post-IV BCG and post-ID MTB-VAC induced PPD-specific IgG avidity and several post-challenge pathology scores in NHPs highlights the potential role of antibodies as protective correlates in TB. In sum, this research underscores the significance of antibody responses and serological as-says in informing and accelerating TB vaccine design. Future endeavours should adopt a holistic approach to antibody profiling, offering new avenues for effective vaccine development and evaluation.